Determination of heavy metals in tomato (Solanum lycopersicum) and their risk to human health - Castillo, José (2022)
Heavy metals generate adverse effects on health at different levels, including, for some metals, the carcinogenic effect, which is why the presence of these substances in food for many countries such as Peru, is considered a public health problem. The objective of this study was to evaluate the health risk associated with the consumption of tomato (Solanum lycopersicum) with the presence of heavy metals such as arsenic and lead in metropolitan Lima. Thirty samples of tomato were taken from the main supply points in metropolitan Lima and the region of origin was determined. The samples were analyzed by atomic absorption spectrophotometry at the Centro de Información, Control Toxicológico y Apoyo a la Gestión Ambiental - CICOTOX. The mean concentration of arsenic in tomato was 0,1908mg/kg, this level exceeded the standard defined by Mercosur (0,1mg/kg). Likewise, the mean lead concentration was 0,0876mg/Kg; this value exceeded the standard defined by the Codex Alimentarius (0,05mg/Kg). Finally, the human risk (HR) for tomato and squash intake was estimated using the methodology proposed by WHO/PAHO. It was determined that the risk from tomato and squash consumption does not represent a significant risk to human health.